2021
DOI: 10.1609/aaai.v35i8.16900
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Cascade: Confidence Calibration for Improving the Accuracy and Computational Cost of Cascade Inference Systems

Abstract: Recently, deep neural networks have become to be used in a variety of applications. While the accuracy of deep neural networks is increasing, the confidence score, which indicates the reliability of the prediction results, is becoming more important. Deep neural networks are seen as highly accurate but known to be overconfident, making it important to calibrate the confidence score. Many studies have been conducted on confidence calibration. They calibrate the confidence score of the model to match its accurac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…One recently discovered issue is that AI models tend to be overconfident, and we experimentally confirmed that the overconfidence of AI models actually negatively impacted model-cascading systems. This explains why we developed a calibration technique for model-cascading systems [5]. Our technique calibrates the confidence scores of lightweight models by taking into account the accuracy of the original AI model as well as that of the lightweight model, leading to a reduction in redundant data transfer (Fig.…”
Section: Learning To Calibrate the Confidence Of Lightweight Models O...mentioning
confidence: 99%
“…One recently discovered issue is that AI models tend to be overconfident, and we experimentally confirmed that the overconfidence of AI models actually negatively impacted model-cascading systems. This explains why we developed a calibration technique for model-cascading systems [5]. Our technique calibrates the confidence scores of lightweight models by taking into account the accuracy of the original AI model as well as that of the lightweight model, leading to a reduction in redundant data transfer (Fig.…”
Section: Learning To Calibrate the Confidence Of Lightweight Models O...mentioning
confidence: 99%